Development of Preserved Resin Specimen of Arthropod Fauna Blocks as a Media for Biology Learning - Wulandari, Anggun; Andrea, Siti Nur Venes (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Specimen preservation is an effort to maintain the original condition of living creatures so that they can be used for educational and research purposes. There are two ways of preserving, namely wet preservation and dry preservation. This research aims to determine the feasibility of preserved specimens of arthropod fauna block resin as a biology learning medium and to determine students' responses to arthropod fauna block resin preserved specimens as a biology learning medium. The development model carried out in this research is a 4D development model with development procedures including the stages of define, design, develop and disseminate. The trial involved class X MIPA 1 students as test subjects. Data obtained from material experts, media experts, and students were analyzed descriptively to evaluate the suitability of learning media. The feasibility results for preserved resin block specimens of arthropod fauna from material expert validation results were 77.8% with good criteria. In comparison, for media expert validation results the percentage was 88.8% with excellent criteria. Meanwhile, data from student responses, and learning media in the form of preserved specimens of resin blocks of arthropod fauna, received very interesting criteria with a percentage of 92%. This research is expected to produce preserved specimens of resin blocks of arthropod fauna that are suitable for use as biology learning media, by the needs of students and technological developments in the world of education.